Accelerating the Domain Green's Function Method through adaptive cross approximation - Ludick, D.; Maaskant, R.; Davidson, David; Jakobus, U. (2014)
© 2014 IEEE. The Domain Green's Function Method (DGFM) is a Method-of-Moments (MoM) based domain decomposition approach that is useful for the analysis of large, irregular antenna arrays. Mutual coupling between array elements is accounted for with the formulation of an active impedance matrix equation for each of the domains/array elements. The active current distribution on the entire array geometry is then obtained by solving these smaller matrix equations pertaining to the elements. The active impedance matrix calculation entails a summation of the MoM matrix diagonal and off-diagonal sub-matrices. For arrays containing a large number of elements this summation can lead to matrix fill times similar to that of the global MoM calculation. To mitigate this significant computational overhead, while still maintaining a sufficient degree of accuracy, the adaptive cross approximation (ACA) algorithm is applied to accelerate this part of the DGFM.